Mobile device remote tracking and lock - Yeo, Ivan You Wei. (2013)
As Mobile devices become an essential necessity in our daily lifestyle, having a secured storage for our privacy data has been deemed to be very significant to the users. Mobile protection has thus become increasingly important in securing privacy data. In the event of stolen or lost phone, sensitive and confidential data will often be intruded and retrieved.